2013
DOI: 10.1002/pip.2454
|View full text |Cite
|
Sign up to set email alerts
|

100-period, 1.23-eV bandgap InGaAs/GaAsP quantum wells for high-efficiency GaAs solar cells: toward current-matched Ge-based tandem cells

Abstract: Major challenges for InGaAs/GaAsP multiple quantum well (MQW) solar cells include both the difficulty in designing suitable structures and, because of the strain-balancing requirement, growing high-quality crystals. The present paper proposes a comprehensive design principle for MQWs that overcomes the trade-off between light absorption and carrier transport that is based, in particular, on a systematical investigation of GaAsP barrier effects on carrier dynamics that occur for various barrier widths and heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 37 publications
2
55
0
6
Order By: Relevance
“…Finally, it has been suggested above that a large number of QWs should provide a higher absorption and therefore higher photocurrent 27,28 However, it is also found that the open circuit voltage decreases with the number of wells due to higher non-radiative dark current, balancing the benefits of including more QWs 29 . This effect would be more severe for deep or lower quality QWs, when dark current is higher and mobilities, lower.…”
Section: Carrier Collection Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it has been suggested above that a large number of QWs should provide a higher absorption and therefore higher photocurrent 27,28 However, it is also found that the open circuit voltage decreases with the number of wells due to higher non-radiative dark current, balancing the benefits of including more QWs 29 . This effect would be more severe for deep or lower quality QWs, when dark current is higher and mobilities, lower.…”
Section: Carrier Collection Efficiencymentioning
confidence: 99%
“…Fujii et al reported in 2013 a MQW structure with 100 periods, a QE of near 75% and with an absorption edge at 1.23 eV 27 . Their performance as a solar cell when illuminated with filtered light (E<1.86 eV) showed an I sc = 12.1 mA/cm 2 , V oc =0.823 and FF=74.6%.…”
Section: State Of the Art Mqw Solar Cellsmentioning
confidence: 99%
“…These devices have been demonstrated mostly on GaAs substrates, but high-quality InGaAs/GaAsP SLs are required to be grown on Ge substrates for Ge-based devices as multi-junction solar cells [12,13]. Substituting GaAs substrates with Ge substrates can also simply contribute to cost reduction.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] и демонстрируют качественно улучшенные характеристики по сравнению с приборами на объемных слоях. При этом ввиду малой толщины слоев КЯ их можно выполнять из материалов не согласованных по параметру решетки с подложкой без релаксации упругих напряжений.…”
Section: Introductionunclassified